2010
DOI: 10.1515/cclm.2010.292
|View full text |Cite
|
Sign up to set email alerts
|

Automated reticulocyte counting: state of the art and clinical applications in the evaluation of erythropoiesis

Abstract: The reticulocyte count reflects the erythropoietic activity of the bone marrow and is thus useful in both the diagnosis of anemias and in monitoring bone marrow response to therapy. Starting in the mid-1990s, automated flow-cytometric analysis has replaced traditional microscopic quantitation of reticulocytes. Reticulocyte analysis now includes measurements mRNA content and the maturity of reticulocytes, cell volume, hemoglobin concentration and content. The immature reticulocyte fraction is a reliable early p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
73
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 71 publications
4
73
1
3
Order By: Relevance
“…Compared to manual reticulocyte counting, flow cytometry was found to be much more precise and enabled improved reticulocyte enumeration of abnormally low counts [39] . A recent review article confirmed the superiority of automated, flow cytometric methods, in particular methods using fluorescent dyes [40] . However, standardization of the reticulocyte count is not yet satisfactory, meaning that instrument-specific reference ranges are still necessary [40] .…”
Section: Major Categories Of Lh Papers In Chronological Ordermentioning
confidence: 90%
“…Compared to manual reticulocyte counting, flow cytometry was found to be much more precise and enabled improved reticulocyte enumeration of abnormally low counts [39] . A recent review article confirmed the superiority of automated, flow cytometric methods, in particular methods using fluorescent dyes [40] . However, standardization of the reticulocyte count is not yet satisfactory, meaning that instrument-specific reference ranges are still necessary [40] .…”
Section: Major Categories Of Lh Papers In Chronological Ordermentioning
confidence: 90%
“…In subsequent microscopic evaluation, reticulocytes can be discriminated from mature red blood cells by an intracellular deep blue precipitate. Nowadays, state-of-the-art hematology automatic counters replace the labor intensive microscopic evaluation of reticulocytes with quick and reliable enumeration of reticulocytes in whole blood samples [2]. The technique is based on specific dyes, which mostly are poly nucleotide-specific, thus binding DNA as well as RNA [2].…”
mentioning
confidence: 99%
“…Nowadays, state-of-the-art hematology automatic counters replace the labor intensive microscopic evaluation of reticulocytes with quick and reliable enumeration of reticulocytes in whole blood samples [2]. The technique is based on specific dyes, which mostly are poly nucleotide-specific, thus binding DNA as well as RNA [2]. Here, we describe a recently observed case where two out of three state-of-theart hematology analyzers displayed a strong discrepancy with manual counting in reticulocyte enumeration due to the presence of Howell Jolly bodies.…”
mentioning
confidence: 99%
See 2 more Smart Citations